2011
DOI: 10.1073/pnas.1013547108
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism for graded motor control encoded in the channel properties of the muscle ACh receptor

Abstract: The larva of the invertebrate chordate Ciona intestinalis possesses only 36 striated muscle cells and lacks body segmentation. It can swim, however, like a vertebrate tadpole, and how its simple body achieves such sophisticated motor control remains puzzling. We found that muscle contractions in Ciona larvae are variable and can be changed by sensory stimuli, so that neuromuscular transmission can convert the variable neural inputs into graded muscle activity. We characterized the molecular nature of the nicot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 38 publications
(70 reference statements)
1
62
0
Order By: Relevance
“…The strong but partial paralysis of Oikopleura observed following ChAT/VAChT knockdown supports the current assumption that excitatory neuromuscular transmission in tunicates is cholinergic as in vertebrates (Ohmori and Sasaki, , Søviknes et al, Nishino et al, ), although there is also immunohistochemical evidence for a neuromuscular function of GABA (Bollner et al, , and see below). A significant drop of acetylcholine production and vesicular storage is expected from the observed fourfold reduction of ChAT transcripts and twofold reduction of VAChT transcripts.…”
Section: Discussionsupporting
confidence: 68%
“…The strong but partial paralysis of Oikopleura observed following ChAT/VAChT knockdown supports the current assumption that excitatory neuromuscular transmission in tunicates is cholinergic as in vertebrates (Ohmori and Sasaki, , Søviknes et al, Nishino et al, ), although there is also immunohistochemical evidence for a neuromuscular function of GABA (Bollner et al, , and see below). A significant drop of acetylcholine production and vesicular storage is expected from the observed fourfold reduction of ChAT transcripts and twofold reduction of VAChT transcripts.…”
Section: Discussionsupporting
confidence: 68%
“…In this study, we identified cell types of gnrh2-expressing cells and visualized their activity in the Ciona larva. Previously, the cells expressing GnRH-encoding genes had been only partially Cholinergic neurons in the motor ganglion have been implicated in the regulation of tail muscle contraction (Horie et al 2010;Nishino et al 2010Nishino et al , 2011Kusakabe 2017). Here we show that one subtype of cholinergic neurons in the motor ganglion expresses gnrh2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…; Nishino et al . , ). Improvements in the functional analyses of neurons have been reported in model organisms for which transgenes are devised for visualizing and controlling the physiology of neurons, as exemplified by calcium indicators, neurotoxins and optogenetic tools (Sweeney et al .…”
Section: Future Perspectivesmentioning
confidence: 99%